The Clinical Efficacy and Safety of Gumiganghwal-Tang in Knee Osteoarthritis: A Phase II Randomized Double Blind Placebo Controlled Study. (14th November 2018) - Chang, Sung Hae; Song, Yun-Kyung; Nah, Seong-Su
Abstract : Background . Gumiganghwal-tang (GMGHT) is a traditional herbal medicine consisting of nine different herbs. GMGHT inhibits the mRNA expression and production of inflammatory cytokines tumor necrosis factor- α (TNF- α ), interleukin-6 (IL-6), and TNF- β on lipopolysaccharide- (LPS-) stimulated peritoneal macrophages in a dose-dependent manner. It is empirically used for the treatment of inflammatory disease, but there are few reports of clinical trials that investigate its efficacy and safety. The current study aimed to investigate the clinical efficacy and safety of GMGHT in patients with knee osteoarthritis (OA). Methods . This was a multicenter, two-armed, double-blinded, randomized, placebo controlled study of GMGHT over 6 weeks. Eligible patients who fulfilled the American College of Rheumatology criteria for OA were randomized to receive either GMGHT or the placebo. Clinical assessments included measurement of knee pain and function using the Western Ontario and McMaster Universities Osteoarthritis Index (WOMAC), patient global assessment (PGA), and knee pain scores every 2 weeks. Results . A total of 128 patients were enrolled (91.4% female; mean age, 58.7 ± 8.1 years). At baseline, pain visual analogue score (VAS) was 67.2 ± 1.4, resp. 71.3 ± 1.6 (treatment, resp. placebo group, p=0.84), and total WOMAC score was 55.2 ± 1.6, resp. 55.6 ± 1.5 (p = 0.84). After 6 weeks, the pain VAS was 43.0 ± 2.5, resp. 61.6 ± 2.5 (p < 0.01) and the total WOMAC score was 34.1 ± 2.4, resp. 46.9 ± 1.8 (p < 0.01). No patients withdrew because of treatment emergent adverse events. Expected adverse events including dyspepsia, liver function abnormality, and lower extremity edema were comparable between both groups. Conclusions . Treatment with GMGHT resulted in significant improvement in pain, function, and global assessment, and it was generally safe and well tolerated in patients with OA.